As Simple as a Broom? - Ducca Durán, Isabel (2025)
A household object such as a broom is imbued with symbolism and magic because of its social circulation. In this chronicle, two fictional stories are developed to counteract the antagonistic perspectives regarding the presence of the broom in the lives of two healing figures: a saint of the Catholic Church and an indigenous midwife in colonial Peru. Tradition has sanctified the broom of the saint and satanized the broom of women, who were accused of being witches. It is concluded with a reference to commodity fetishism, as the origin of demonizing the broom was an economic process. Women accused of being witches were stripped of their property, their productive capacity, and their knowledge